Pregunta
Which of the following expressions are equivalent to \( 6+(-4)-5 \) ? Choose 2 answers: A \( 6-4-(-5) \) B \( 6+4-5 \) C \( -5+6-4 \) D \( -4+(-5)+6 \)
Ask by Munoz Pritchard. in the United States
Feb 03,2025
Solución de tutoría real
Respuesta verificada por el tutor
Responder
Options C and D are equivalent to \( 6 + (-4) - 5 \).
Solución
To determine which expressions are equivalent to \( 6 + (-4) - 5 \), let's simplify the original expression first:
\[
6 + (-4) - 5 = 6 - 4 - 5 = 2 - 5 = -3
\]
Now, evaluate each option:
**A. \( 6 - 4 - (-5) \)**
\[
6 - 4 - (-5) = 6 - 4 + 5 = 2 + 5 = 7 \quad (\text{Not equal to } -3)
\]
**B. \( 6 + 4 - 5 \)**
\[
6 + 4 - 5 = 10 - 5 = 5 \quad (\text{Not equal to } -3)
\]
**C. \( -5 + 6 - 4 \)**
\[
-5 + 6 - 4 = 1 - 4 = -3 \quad (\text{Equal to } -3)
\]
**D. \( -4 + (-5) + 6 \)**
\[
-4 + (-5) + 6 = -9 + 6 = -3 \quad (\text{Equal to } -3)
\]
Therefore, **options C and D** are equivalent to \( 6 + (-4) - 5 \).
**Answer:** Options C and D
Revisado y aprobado por el equipo de tutoría de UpStudy
Como
error msg
Explicar
Simplifique esta solución
Mind Expander
To evaluate \( 6 + (-4) - 5 \), let's simplify it step by step. First, \( 6 + (-4) \) is the same as \( 6 - 4 = 2 \). Next, subtracting 5 gives us \( 2 - 5 = -3 \). Now, let's check which options also yield \(-3\): A) \( 6 - 4 - (-5) = 6 - 4 + 5 = 2 + 5 = 7 \) (not equivalent) B) \( 6 + 4 - 5 = 10 - 5 = 5 \) (not equivalent) C) \( -5 + 6 - 4 = 1 - 4 = -3 \) (equivalent) D) \( -4 + (-5) + 6 = -9 + 6 = -3 \) (equivalent) So the equivalent expressions are C and D! 🎉
¡Prueba Premium ahora!
¡Prueba Premium y hazle a Thoth AI preguntas de matemáticas ilimitadas ahora!
Quizas mas tarde
Hazte Premium